Hacking exposed unified communications & VoIP security secrets & solutions - Collier, Mark D.; Endler, David (McGraw-Hill Education, 2014)
Establish a holistic security stance by learning to view your Internet telephony infrastructure through the eyes of the nefarious cyber-criminal. Hacking ExposedTM Unified Communications & VoIP, Second Edition offers thoroughly expanded coverage of today's rampant threats alongside ready-to-deploy countermeasures. Find out how to block TDoS, toll and social engineering fraud, service abuse, voice phishing, voice SPAM/SPIT, eavesdropping, and man-in-the-middle exploits. This comprehensive guide features all-new chapters, case studies, and examples.